The Nimrud Letters, 1952 – Part VIII: Imperial Administration - Saggs, H. W. F.
Nimrud Letters LXXXV-XCV; ND 2070; ND 2356; ND 2625; ND 2495; ND 2631; ND 2382; ND 2418; ND 2642; ND 2742; ND 2637; ND 2800.